Structure of air chemical pollution and environmental zoning for health assessment in large industrial centre - M. V. Tabakaev; S. A. Maksimov; E. B. Shapovalova; G. V. Artamonova (Acta Biomedica Scientifica)
The problem of contamination of the lower layer of the atmosphere in Western Siberia remains relevant more than half a century. The territory of the city of Kemerovo, a major industrial center with well-developed coal-chemical complex is an obvious example of antropotechnogenous burden on the environment and the health of the population with its climatic and geographical, weather and economic features. The aim of the study was to evaluate the structure of chemical contamination during 2005-2011 years, their interaction and the allocation of the factors that determine the ecological zoning on the example of the city of Kemerovo to identify the role of chemical pollution on the health of the population. Factor analysis revealed two latentfactors that determine the structuring of chemical pollution of the city of Kemerovo, in accordance with the wind rose and the chemical nature of the contaminants. The research shows the negative influence of chemical pollution on the health of the population of the city of Kemerovo.